Effect of L-Threonine Supplementation to Diet on Some Productive and Physiological of Traits Broiler Chickens Under Heat Stress Conditions - Wasman, Pakiza Hamira (Diyala Agricultural Sciences Journal, 2022)
This experiment was conducted in Erbil, Iraq, from July 7 to August 17, 2021, for determine the effects of L Threonine supplementation on several productive and physiological traits Under heat stress conditions (36.04 ± 2 °C), A total of 200 broiler chicks were randomly distributed into five treatments: T1 control treatment, T2, T3, T4 and T5 standard diet with L-Threonine 250, 500, 750 and 1000 mg/kg, respectively. The results showed that the addition of L-Threonine to the ration improved broiler production performance under heat stress conditions such as body weight it increased significantly (P≤0.05) in T3 and T5 and reached 2187 and 2235 g, respectively compared to 2145 g in the T1 and reduce H/L ratio in T4 and T5 compared with T1 and did not affect effect (P≥0.05) on physiological traits such as red and white blood cell count, hematocrit, cholesterol, glucose, total protein, aspartate aminotransferase and alanine aminotransferase activities.